Efektifitas Bahan Ajar Panduan PembelajaranKebencanaan Di Kabupaten Klaten Pada BencanaAngin Putting Beliung Melalui StrategiSnowball Throwing Di SMA N 2 Klaten - Wiga Saputro, Seno, Drs.Muhammad Musiyam,M.T.P (2016)
This study aims to (1) determine improving student learning outcomes after learning of disaster using teaching materials Handbook Kebencaan Klaten district with strategies snowball thrawing, (2) determine the effectiveness of teaching materials book "Free Learning disaster Klaten regency" in cyclones in learning in SMAN 2 Klaten disaster through throwing snowball strategy. This research is a qualitative research. Designs in this study using an experimental method. The design used One- Gruop pretest-posttest design. Data collection techniques using observation, tests and documents. Persyrata test technique using the analytical instrument validity test, reliability test instrument test, normality test and test hypotheses. Data analysis techniques in this study daalah quantitative descriptive. Based on the research that has been done, it can be concluded that (1) In the normality test is done the result shows significant value is in the data distribution control pretest known class of data Asymp. Sig. (2-taled) amounted to 0.237, thus the data Asymp. Sig (2-taled) is greater than 0.05, then it can be concluded that the distribution and control class pretest including normal distribution of data. Normality test results in a data distribution control posttes known class of data Asymp. Sig. (2-taled) amounted to 0.181, thus the data Asymp. Sig (2-taled) is greater than 0.05, then it can be concluded that the distribution and control class pretest including normal distribution of data. (2) Results of normality test on the distribution of data pretest experimental class of data known Asymp. Sig. (2-taled) amounted to 0.389, thus the data Asymp. Sig (2-taled) is greater than 0.05, then it can be concluded that the distribution and pretest the experimental class includes normal distribution of data. Normality test results on the distribution of data posttes known experimental class of data Asymp. Sig. (2-taled) amounted to 0.181, thus the data Asymp. Sig (2-taled) is greater than 0.05, then it can be concluded that the distribution and pretest the experimental class includes normal distribution of data. (3) learning on the learner show improvement before and after using the snowball strategy thrawing, if learning using the conventional method of lectures in class control shows the results of value - average 62.22, and after learning by using the snowball strategy thrawing, show results the average value increased to 70, so there is an increase learning outcomes before and after using conventional methods and strategies snowball thrawing increased. , So we can conclude, that the guidebooks disaster typhoons material using thrawing snowball strategy in learning is more effective than using the conventional method of the lecture with the same teaching materials. Keywords: Snowball Strategy Thrawing, Effectiveness, Hurricane, Instructional Materials.